2007
DOI: 10.1007/s10533-007-9116-0
|View full text |Cite
|
Sign up to set email alerts
|

Benthic sediment influence on dissolved phosphorus concentrations in a headwater stream

Abstract: Phosphate interacts with inorganic sediment particles through sorption reactions in streams. Collectively, this phosphorus (P) buffering mechanism can be an important determinant of soluble reactive P (SRP) concentrations. If sorption reactions control SRP concentrations in a stream, then differences in sediment characteristics may cause spatial differences in SRP concentrations. This prediction was tested by examining sediment-buffering characteristics and spatial variation in SRP among reaches with distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 45 publications
1
40
1
3
Order By: Relevance
“…One hypothesis for this observation is simply P limitation of floodplain streams, as has been observed in the Alaskan tundra (Peterson et al 1985;Slavik et al 2004). Alternatively, this pattern may be the result of high physical sorption of P (Lottig & Stanley 2007) and low biological uptake of nutrients in floodplain streams relative to upland streams. Results of sorption experiments support this conclusion, suggesting that biological uptake of P in upland streams is threefold higher than in floodplain streams and that nearly all P uptake in floodplain streams was explained by physical processes (ca.…”
Section: Nutrient Spiralling Metricsmentioning
confidence: 79%
See 2 more Smart Citations
“…One hypothesis for this observation is simply P limitation of floodplain streams, as has been observed in the Alaskan tundra (Peterson et al 1985;Slavik et al 2004). Alternatively, this pattern may be the result of high physical sorption of P (Lottig & Stanley 2007) and low biological uptake of nutrients in floodplain streams relative to upland streams. Results of sorption experiments support this conclusion, suggesting that biological uptake of P in upland streams is threefold higher than in floodplain streams and that nearly all P uptake in floodplain streams was explained by physical processes (ca.…”
Section: Nutrient Spiralling Metricsmentioning
confidence: 79%
“…It seems quite likely that increasing organic matter and nutrient inputs will stimulate biological activity to a greater degree than physical processes (Lottig & Stanley 2007), which may lead to larger changes in organic matter and nutrient dynamics in upland streams. This may result in very different spatial and temporal patterns in nutrient export downstream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At both Siloam and Tahlequah, within-river retention of effluent TP dropped dramatically (by a factor of c. 9) after 2002, as a result of enhanced nutrient removal at Springdale WWTP and the resulting reductions in effluent P input loading. Earlier studies have suggested that P uptake by periphyton exerts a major control on withinriver P retention in the Illinois River 54 . The decline in P retention with decreasing effluent P load also suggests a biological control mechanism: reductions in effluent P inputs may reduce the periphyton biomass that can be supported, thus leading to a decline in P retention.…”
Section: Within-river Retention Of Effluent Tp Loadsmentioning
confidence: 99%
“…The transport and storage of P in drainage ditches involve complex biogeochemical processes [3,10]. Of all the components that affect nutrient dynamics and transport in aquatic ecosystems, benthic sediments are probably the most influential determinant of the ability of the system to process and sustain nutrient loads, especially P [7,11,12]. Sediments play an active role in inorganic P uptake and may potentially control P concentrations in the overlying water column [1,12,13].…”
Section: Introductionmentioning
confidence: 99%